Creativity and sociology
1 online resource (xi, 252 pages)
Keywords: "Creativity and Sociology: Doing Social Research with and on Artistic Sources explores the relationship between artistic and sociological narratives, considering the ways in which artistic narratives in their different forms can be both subjects of sociological observation and tools for the sociological analysis of reality. Thematically divided into sections that focus on 'doing sociology on art' and 'doing sociology with art', it observes the major forms of art - including literature, music, theatre, painting, photography, cinematography and interactive arts such as videogames - examining each as objects and instruments of sociological analysis: as narratives that can offer new perspectives on the world. Bringing together under a single epistemological framework area of research that frequently remain separate, or beyond sociological framing, this book will appeal to scholars of sociology, social theory and social science methodology with interests in media and artistic narratives"-- Provided by publisher.